Physicochemical Analysis of Bembal River Water in Lau Local Government Area, Taraba State, Nigeria - Ibrahim, John; Kefas, Mathias; Gaude, Joshua Jesse; Ezekiel, Buzi (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The study investigated various physicochemical parameters in the Bembal River, Lau, Taraba state, Nigeria over six months. The study was carried out in the Bembal River, which is located in the Lau local government area, Taraba state. Samples of water were taken fortnightly throughout six (6) months (i.e. from November 2023 to April, 2024) from 6 am local time. Water samples were collected and transported to the laboratory for physicochemical parameters. Results of the physiochemical parameters were in the range of 23.60 to 25.90°C (water temperature), 12.68 to 37.21cm (Transparency ), 6.66 to 7.56 (pH), 83.00mg/L to 91.67mg/L (Total Alkalinity ), 69.94 to 155.208 us/ cm (water conductivity), 5.30 to 17.46mg/l (free CO2 ), 27.50 to 34.50mg/l (Nitrate ), 118.22 to 145.12mg/l (Phosphate ), 0.0054 to 0.069mg/l (Ammonia), 0.61 to 1.85mg/l (Dissolved Oxygen ), 78.70 to 83.44mg/L (Dissolved solids ), 3.14 to 4.081mg/L (Biochemical oxygen demand ). All the physicochemical parameters showed significant differences in variability with the months (P < 0.05). Based on the findings for this study, the physicochemical parameters such as phosphate, free CO2, Ammonia, BOD and DO were recorded above the recommended limit, while the rest of the parameters were within the range. However, a routine monitoring of these parameters in this study area has to be carried out to ascertain the long-term impact of anthropogenic inputs to take remedial measures to ensure the good health of aquatic life.